PENANAMAN NILAI-NILAI FILANTROPI MELALU KEGIATAN INFAK DAN SEDEKAH DI SMP NEGERI 4 LAIS - Brenda Yakuta; Alimron Alimron; Romli Romli (Jurnal PAI Raden Fatah, 2022)
This thesis discusses "planting philanthropic values ​​through infaq and alms activities at SMP Negeri 4 Lais". The background in this research is the lack of understanding in instilling philanthropic values ​​in students so the process of implementing Infak and Alms is still not running effectively. The purpose of this research is to find out the inculcation of philanthropic values ​​through infaq and alms activities and to find out what are the supporting and inhibiting factors of the activities carried out by students carrying out infaq and alms. This study uses qualitative methods using observation, interviews, and documentation. Then, the researcher will use data analysis techniques, namely the process of creating, searching, and finding data which is then arranged regularly on the data that has been obtained both from observations, interviews, and documentation. Then the researcher will choose what data is important and studied. Then the last researcher will make research conclusions that are useful so that they are easily understood by researchers and others. The research results obtained are: First, the process of instilling philanthropic values ​​through infaq and alms activities at SMP Negeri 4 Lais has been instilled by the principal and teachers to students. However, the family and community environment also affects infaq and alms. Second, supporting factors in providing philanthropic values ​​to students are not only carried out by school principals, educators, and students but are carried out by students' guardians so that philanthropic values ​​can be embedded from an early age. Third, the obstacles that exist in the process of instilling philanthropic values ​​through infaq and alms activities, due to a lack of awareness about religion and understanding of philanthropy, a lack of sense of responsibility for students and economic conditions, and awareness of guardians of students.